Amending legislatures in authoritarian regimes: power sharing in post-Soviet Eurasia. Issue 3 (3rd April 2021) - Krol, Gerrit
ABSTRACT: A large body of scholarship points to the importance of legislatures in authoritarian regimes, arguably making them more stable and durable. Legislatures could, for example, perform a co-opting function by giving legislative power to potential opponents of incumbents. Additional evidence is needed, however, to show that this legislative function of parliament exists in non-democracies. This article, therefore, takes a step back and investigates to what extent parliaments in authoritarian regimes have a legislative function, by focusing on the amendment of executive bills. Based on an innovative way of measuring parliamentary amendment, the analysis uses a unique original dataset with cross-national data on 5271 executive bills from Russia, Kazakhstan, Ukraine and Kyrgyzstan. The figures demonstrate a high level of activity across all parliaments analysed here. Importantly, however, some legislatures are more active than others. Contributing empirically and theoretically to existing literature, the results show that legislatures on average amend executive bills for 43.2% and that power sharing institutions, defined as contestation and institutional differentiation, constitute mechanisms causing different levels of activity. The article concludes by discussing the limitations of the investigation and indicates where future research could strengthen further theoretical and empirical links between legislative power sharing, co-optation and regime stability.